Is subclinical hypothyroidism associated with cardiovascular disease in the elderly? - Koichiro Yamamoto; Yasuhiro Nakano; Yoshiaki Soejima; Atsuhito Suyama; Kohei Oguni; Kou Hasegawa; Fumio Otsuka (Endocrine Connections)
Subclinical hypothyroidism (SCH) is diagnosed when thyroid function tests show that the serum thyrotropin (TSH) level is elevated and the serum free thyroxine (FT4) level is normal. SCH is mainly caused by Hashimoto’s thyroiditis, the prevalence of which increases with aging. Recently, it has been revealed that SCH is associated with risk factors for cardiovascular diseases (CVDs), including atherosclerosis, dyslipidemia and hypertension, leading to cardiovascular morbidity and mortality. However, there are still controversies regarding the diagnosis and treatment of SCH in elderly patients. In this review, we present recent evidence regarding the relationship between SCH and CVD and treatment recommendations for SCH, especially in elderly patients. Studies have shown that SCH is associated with CVD and all-cause mortality. Patients aged less than 65 years showed significant associations of SCH with CVD risk and all-cause mortality, whereas patients aged 65 or older did not show such associations. It was shown that levothyroxine therapy was associated with lower all-cause mortality and cardiovascular mortality in younger SCH patients (<65–70 years) but not in SCH patients aged 65–70 years or older. In elderly SCH patients, levothyroxine treatment should be considered individually according to the patient’s age, serum TSH level, hypothyroid symptoms, CVD risk and other comorbidities. To further elucidate the impact of SCH on CVD in elderly patients, studies should be conducted using age-specific reference ranges of results of thyroid function tests, focusing on elderly patients, specific serum TSH levels, thyroid antibody status and cardiovascular risk factors.